Produtividade da soja em terras baixas em diferentes declividades do sistema sulco/camalhão - (:unkn) unknown (Universidade Federal do Pampa, 2021)
The use of soil management techniques that provide a better environment for plant development is critical for successful lowland crop rotation. Based on this, the present study sought to evaluate the use of the furrow/ridge system under four slopes, without the use of irrigation in soybean cultivation. The experiment was arranged in a randomized block design with split plots and four replications. The main portion being the different slopes of 0.0%; 0.25%; 0.5%; 1.0%. And the subplot was the location in the plots that were divided into 3 points, beginning, middle and end. This division was carried out because the water runoff time at the beginning of the plot is shorter than at the end. The following soil attributes were evaluated: Soil density, total porosity, macroporosity, microporosity, saturated soil hydraulic conductivity and soil moisture. Plant development was evaluated by established plant population, leaf chlorophyll content and grain yield. The treatments did not influence the physical-water indices of the soil. The number of established plants increases as the slope of the furrow increases, with 0% treatment differing statistically from 1%. Despite differences in chlorophyll content, it was not possible to observe a clear trend in the results. The soil moisture in the 1% treatment at the end of the plot was 40.6% higher than at the beginning. In years withlow rainfall, soil management focused on drainage does not interfere with soybean yield.
Keywords: Engenharia agrícola; Solo - Uso; Drenagem; Terras baixas; Soja; Agricultural engineering; Soil - Use; Drainage; Lowlands; Soy; CNPQ::CIENCIAS AGRARIAS